Неизвестная личинка жука-листоеда рода Chrysolina (Coleoptera, Chrysomelidae) с Кавказа - Охрименко, Н.В. (Вестник зоологии, 1993)
A description of Chrysolina cuprina D u f t., larva, ecological, trophic and distributional data.